METODE DISCOVERY LEARNING PADA MATA KULIAH METODE PENELITIAN SOSIAL DI PROGRAM STUDI PENDIDIKAN SEJARAH STKIP PGRI SUMATERA BARAT - Zusmelia, Zusmelia; Zulfa, Zulfa (Jurnal Pelangi : Research of Education and Development, 2014)
The learning of Social Research Method subject has always had difficulties since the low of student’s creativity in seeking and finding the problem. The students prefer to cooperate in finding the problem of the subject. It is one of the reasons for the Lecturer to do a Classroom Action Research (CAR). CAR is conducted by using a Discovery Learning method. This method is a learning model developed based on the constructivism. It emphasizes the necessity of the important structures or ideas to a discipline by having an active student involvement in the learning process. On this subject, a student is required to seek and find out the problems. CAR is a reflected research of the actions taken by the Lecturers to improve the learning process as one of their responsibilities